Clinical relevance of genetic variants of gonadotrophins and their receptors in controlled ovarian stimulation: a systematic review and meta-analysis. (18th June 2018) - Alviggi, Carlo; Conforti, Alessandro; Santi, Daniele; Esteves, Sandro C; Andersen, Claus Yding; Humaidan, Peter; Chiodini, Paolo; De Placido, Giuseppe; Simoni, Manuela
Abstract: BACKGROUND: Genotype has been implicated in the outcome of ovarian stimulation. The analysis of patient-specific genotypes might lead to an individualized pharmacogenomic approach to controlled ovarian stimulation (COS). However, the validity of such an approach remains to be established. OBJECTIVE AND RATIONALE: To define the impact of specific genotype profiles of follicle-stimulating hormone, luteinizing hormone and their receptors (FSHR, LHR and LHCGR) on ovarian stimulation outcome. Specifically, our aim was to identify polymorphisms that could be useful in clinical practice, and those that need further clinical investigation. SEARCH METHODS: A systematic review followed by a meta-analysis was performed according to the Cochrane Collaboration and Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines without time restriction. We searched the PubMed/MEDLINE, Cochrane Library, SCOPUS and EMBASE databases to identify all relevant studies published before January 2017. Only clinical trials published as full-text articles in peer-reviewed journals were included. The primary outcome was the number of oocytes retrieved. OUTCOMES: Fifty-seven studies were assessed for eligibility, 33 of which were included in the qualitative and quantitative analyses. Data were independently extracted using quality indicators. COS outcomes related to seven polymorphisms ( FSHR [rs6165], FSHR [rs6166], FSHR [rs1394205], LHB [rs1800447], LHB [rs1056917], LHCGR [rs2293275] and LHCGR [rs13405728]) were evaluated. More oocytes were retrieved from FSHR (rs6165) AA homozygotes (five studies, 677 patients, weighted mean difference [WMD]: 1.85, 95% CI: 0.85–2.85, P < 0.001; I 2 = 0%) than from GG homozygotes and AG heterozygotes (four studies, 630 patients, WMD: 1.62, 95% CI: 0.28–2.95, P = 0.020; I 2 = 56%). Moreover, stimulation duration was shorter in FSHR (rs6165) AA homozygotes than in AG carriers (three studies, 588 patients, WMD −0.48, 95% CI: −0.87 to −0.10, P = 0.010, I 2 = 44%). A higher number of oocytes (21 studies, 2632 patients WMD: 0.84, 95% CI: 0.19 to 1.49, P = 0.01, I 2 = 76%) and metaphase II oocytes (five studies, 608 patients, WMD: 1.03, 95% CI: 0.01–2.05, P = 0.050, I 2 = 0%) was observed in AA than in GG homozygote carriers. FSH consumption was significantly lower in FSHR (rs1394205) GG homozygotes (three studies, 411 patients, WMD: −1294.61 IU, 95% CI: −593.08 to −1996.14 IU, P = 0.0003, I 2 = 99%) and AG heterozygotes (three studies, 367 patients, WMD: −1014.36 IU, 95% CI: −364.11 to −1664.61 IU, P = 0.002, I 2 = 99%) than in AA homozygotes. WIDER IMPLICATIONS: These results support the clinical relevance of specific genotype profiles on reproductive outcome. Further studies are required to determine their application in a pharmacogenomic approach to ovarian stimulation.